2016
DOI: 10.1037/dev0000181
|View full text |Cite
|
Sign up to set email alerts
|

The development of adaptive decision making: Recognition-based inference in children and adolescents.

Abstract: Judgments about objects in the world are often based on probabilistic information (or cues). A frugal judgment strategy that utilizes memory (i.e., the ability to discriminate between known and unknown objects) as a cue for inference is the recognition heuristic (RH). The usefulness of the RH depends on the structure of the environment, particularly the predictive power (validity) of recognition. Little is known about developmental differences in use of the RH. In this study, the authors examined (a) to what e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 65 publications
2
34
2
Order By: Relevance
“…For instance, we used a selection of perceptual stimuli whose arbitrary associations with values had to be learned in an initial study phase. Although this approach provides good experimental control over prior knowledge and stimulus features, it is important to extend the research on cost‐benefit decisions to other environments in which children might use natural associations between real‐world objects (e.g., toys, snacks, or other familiar items) and subjective value, based on individual learning histories (e.g., Horn, Ruggeri, & Pachur, ). It is also an open question whether the current findings generalize to other nonmonetary forms of cost and benefits (beyond point values, tokens, and monetary payoffs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we used a selection of perceptual stimuli whose arbitrary associations with values had to be learned in an initial study phase. Although this approach provides good experimental control over prior knowledge and stimulus features, it is important to extend the research on cost‐benefit decisions to other environments in which children might use natural associations between real‐world objects (e.g., toys, snacks, or other familiar items) and subjective value, based on individual learning histories (e.g., Horn, Ruggeri, & Pachur, ). It is also an open question whether the current findings generalize to other nonmonetary forms of cost and benefits (beyond point values, tokens, and monetary payoffs).…”
Section: Discussionmentioning
confidence: 99%
“…In all present analyses, the upper boundary was associated with "accept" decisions and the lower boundary with "reject" decisions; s was fixed at 1. Adapted with permission from Horn, Bayen, and Smith (2013).…”
Section: Drift-diffusion Modelingmentioning
confidence: 99%
“…Specifically, the r -model provides probability estimates for the reliance on recognition (parameter r ), for the cue validity of further knowledge, and of recognition. Further details are in “ Appendix A ” (Hilbig et al 2010 ; Horn et al 2015 , 2016 ; we also explored a memory-state model extension that did not alter the main conclusions in the present study; see Castela, Kellen, Erdfelder, Hilbig, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…In many real-life situations, decisions have to be made under limited time, and it is known that adults adapt to time limitation using faster and simpler (Ben Zur & Brenitz, 1981;Payne, Bettmann, & Johnson, 1988), but not necessarily more effective (Belling, Suss, & Ward, 2015) strategies. Recent work has shown that children are ecological learnersthey modify their learning strategies to the characteristics of the task at hand (Horn, Ruggeri, & Pachur, 2016;Nelson, Divjak, Gudmundsdottir, Martignon, & Meder, 2014;Ruggeri & Lombrozo, 2015), and they do so already by age 4 (Ruggeri, Sim, & Xu, 2017). The effects of time limitation on the efficiency of children's reasoning are mixed.…”
Section: Time-limitation Effectsmentioning
confidence: 99%